Komunikasi Pemasaran Produk Herbaleo melalui Media Sosial TikTok (Strategi Content Creator) - Athalia, Jennifer Angel; Sukendro, Gregorius Genep (Prologia, 2023)
The development of  digital technology has changed the way a company markets its products. One of them is Herbaleo, which follows digital developments by starting to enter social media TikTok. Herbaleo does product marketing on TikTok with the help of a content creator. As a health brand it is very important for Herbalio to build consumer trust. The author is interested in knowing the marketing communication strategy for Herbaleo content creators in marketing detox tea products on the Herbaleo Detox Tea TikTok account. The author uses a qualitative approach in this study. The data obtained in this study were from semi-structured interviews, participatory observation, documentation, and literature studies. As a result, the content creator strategy in marketing products is by uploading interactive, educative, informative, and entertainment content. In addition, Herbaleo detox tea content creators also collaborate with influencers. Perkembangan teknologi digital yang semakin maju mengubah cara sebuah perusahaan dalam memasarkan produk. Salah satunya Herbaleo yang mengikuti perkembangan digital dengan mulai masuk ke media sosial TikTok. Herbaleo melakukan pemasaran produk di TikTok dengan bantuan seorang content creator. Sebagai brand kesehatan sangat penting bagi Herbalio untuk membangun kepercayaan konsumen. Penulis tertarik untuk mengetahui strategi komunikasi pemasaran content creator Herbaleo dalam memasarkan produk detox tea di akun TikTok Herbaleo Detox Tea. Penulis menggunakan pendekatan kualitatif dalam penelitian ini. Data yang diperoleh pada penelitian ini dari wawancara semi terstruktur, observasi partisipasi, dokumentasi, dan studi kepustakaan. Hasilnya, strategi content creator dalam melakukan pemasaran produk yaitu dengan mengunggah konten interaktif, edukatif, informatif, dan entertainment. Selain itu, content creator Herbaleo detox tea juga melakukan kolaborasi dengan influencer.